Efficiency of an E-Commerce Web Application with MERN Stack and Modern Tools - C.M.K De Silva; A. S De Silva; K.A. I Maduwantha; D.A.I.U Dewpura; D.I.De Silva; R.R.P De Zoysa (International Journal of Engineering and Management Research, 2022)
The majority of people in today's generation use technology to manage their life and take care of their basic necessities. Many of us in our generation shop for clothing, groceries, and electronics and even fancy items via e-commerce websites. We created a single chocolatier e-commerce web application utilizing the MERN stack, which consists of the MongoDB database, the Express.JS framework, the React.JS library, and the Node.JS platform. This program has several views for users and administrators, is fully functioning with 8 main functions. Depending on the interests of the consumer, we can purchase many chocolate types and brands through this website. In this project, we have the option to add and remove, edit, and save various products. For the website, we have created administrative features including login and logout options, admin dashboard, category and brand management for customers, payment method options for carts, review, and promotion management. Customers could search, sort, filter, and add goods to the cart. The customer can pay and purchase the things when the bills are created based on the cart contents. On the other hand, we have used the modern tools which are necessary to improve the functional and non-functional requirements of the application.